Les retours d’une exploration méthodologique croisant données Twitter, recrutement via Facebook et questionnaires web - Emmanuel Ravalet; Jean-François Lucas; Antoine Lohou (Netcom)
The presence of some groups of population on the Internet and the important activity they generate suggest that social scientists think about the methodological perspectives to capture such information. This article aims to report two experiences which both use social networks, respectively Twitter and Facebook, to give some insights on practices and social representations linked with mobility. These methods, on their own and articulated in an original methodological path, have some advantages compared with more classical methods. But some important limits still exist and methodological issues are major.